Bidhan Chilli-4: New dual purpose chilli variety - Chattopadhyay, Arup; Karmakar, Krishna; Dutta, Subrata; Mandal, Asit Kumar; Maurya, Praveen Kumar; Banerjee, Swadesh; Bhattacharjee, Tridip; Hazra, Pranab (Indian Horticulture, 2021)
Bidhan Chilli-4, a semi-prostrate, green fruited with pointed fruit blossom end variety, having high field resistance to pepper leaf curl virus (PepLCV), fruit rot, chilli thrips and yellow mite, has been developed through selection from indigenous collections obtained from Cooch behar district of West Bengal by Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal. This variety has been released by the State Variety Release Committee, West Bengal and notified by the Central Variety Release Committee for State release during 2019. The variety is early maturing, can be fitted well in multiple cropping system, can be used as dual purpose (green and dry), and is high yielding. This variety can perform well in eastern parts of India apart from West Bengal.